Photovoltaic polymers based on difluoroqinoxaline units with deep HOMO levels. Issue 14 (21st April 2018) - Song, Suhee; Keum, Sangha; Lee, Ji‐Hyun; Lee, Jihoon; Kim, Seungmin; Park, Seong Soo; Kim, Jin Young; Park, Sung Heum; Jin, Youngeup
ABSTRACT: We report the synthesis of low bandgap polymers with a difluoroquinoxaline unit by Stille polymerization for use in polymer solar cells (PSCs). A new series of copolymers with 2, 3‐didodecyl‐6, 7‐difluoro quinoxaline as the electron‐deficient unit and alkyloxybenzo[1, 2‐ b :4, 5‐ b′ ]dithiophene and thiophene as the electron‐rich unit were synthesized. The photovoltaic properties of the devices based on the synthesized polymers revealed that the fluorine atoms at the quinoxaline units aid in decreasing the highest occupied molecular orbital (HOMO) energy levels; this in turn increased the open circuit voltage of the devices. The polymers with long alkyl chains exhibited good solubility that increased their molecular weight, but the power conversion efficiency was low. Efficient polymer solar cells were fabricated by blending the synthesized copolymers with PC71 BM, and the PCE increased up to 5.11% under 100 mW cm −2 AM 1.5 illumination. These results demonstrate that the importance of having a control polymer to be synthesized and characterized side by side with the fluorine analogues. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 1489–1497 Abstract : A new series of copolymers with 2, 3‐didodecyl‐6, 7‐difluoro quinoxaline as the electron‐deficient unit and alkyloxybenzo[1, 2‐ b :4, 5‐ b ′]dithiophene and thiophene as the electron‐rich unit were synthesized. The photovoltaic properties of the devices based on the synthesized polymers revealed that the fluorine atoms at the quinoxaline units aid in decreasing the highest occupied molecular orbital (HOMO) energy levels; this in turn increased the open circuit voltage of the devices.